Teacher’s Perceptions and Challenges towards the Use of Flashcards as an Ice-breaking Activity to Help Students Learn to Speak - Firdausi, Annisa Azzahra (RETAIN : Journal of Research in English Language Teaching, 2024)
The ability to speak English is an essential aspect of learning outcomes at all levels, but many students in Indonesia still need help with their speaking skills. One way that teachers can apply to help students learn to speak is by combining fun activities such as ice-breaking with engaging learning media, namely flashcards. This research further aims to describe (1) teacher’s perceptions of the use of flashcards as an ice-breaking activity to help students learn to speak and (2) the challenges faced by teachers when teaching using flashcards as an ice-breaking activity to help students learn to speak. Based on these two research objectives, this research is categorized as descriptive qualitative research. The data in this research are the results of interviews with teachers who use flashcards as an ice-breaking activity to help students learn to speak and the results of class observations during the learning process. Then, the data obtained was analyzed by researchers, and the results of this analysis showed that teachers thought that using flashcards as an ice-breaking activity to help students learn to speak was important, flashcards were also the suitable media to use, and flashcards as an ice-breaking activity could be tools to help students learn to speak. Then, in the implementation process, it was found that teachers only encountered obstacles for a limited time. However, the teacher added that during implementation, students experienced obstacles such as fear, embarrassment, and lack of focus in the learning process.